CORRELATIONAL STUDY BETWEEN LEG MUSCLES EXPLOSIVE POWER, ARM MUSCLES EXPLOSIVE POWER, AND BACK MUSCLES FLEXIBILITY ON VOLLEYBALL SPIKE SKILL TOWARD PHYSICAL EDUCATION STUDENTS OF STKIP PASUNDAN CIMAHI - Rohendi, Aep (Program Pascasarjana Universitas Negeri Jakarta, 2016)
This study aims to reveal the relationship between leg muscles explosive power, arm muscles explosive power, and back muscles flexibility on volleyball spike skill toward physical education students of STKIP PasundanCimahi. The research method used in this study is survey method with the correlational design. This study is correlational. Based on the calculation, there is plural correlation coefficient gained between leg muscles explosive power (X1), arm muscles explosive power (X2), back muscles flexibility (X3), and spike skill (Y) shown by correlational coefficient Ry1.2.3.y = 0.458.Fcalculate= 7,34andFtablewere gained at the real level0.05 = 2.89 after the tests of significance was carried out. Thus the plural correlation between leg muscles explosive power (X1), arm muscles explosive power (X2), and back muscles flexibility (X3), together with the spike skill (Y) is significant.